Constitutive models for nonlinear analysis of SFRC corbels. (March 2020) - Beshara, F.B.A.; Mustafa, T.S.; Mahmoud, A.A.; Khalil, M.M.A.
Abstract: In this paper, nonlinear constitutive models are proposed for steel fiber reinforced concrete (SFRC) in compression and tension. The models were implemented in the finite element computer program ANSYS for 3-D nonlinear analysis of SFRC corbels under monotonic static loading. Several validation studies have been performed for normal-strength and high-strength SFRC corbels with constant or variable depth. Good agreement is generally achieved between experimental and numerical results for the load-deflection curves and crack patterns. Additionally, parametric studies have been performed in order to investigate the effect of structural parameters on the performance of SFRC corbels. It was found that: (1) increasing the concrete compressive strength ( f c ' ) improves corbel shear capacity and toughness, (2) the inclusion of steel fiber ( V f ) delays premature shear failure for corbels and enhances strain ductility, (3) an enhancement in shear capacity and strain ductility is noticed by increasing the ratio of horizontal stirrups ( ρ h ), and finally, (4) increasing the shear span-to-depth ratio ( a/d ) reduces the shear capacity of SFRC corbels. Corbel shear capacity increases by 27% due to a 33% increase in ( f c ' ), by 31% due to V f = 1% inclusion, by 20% due to a 1% increase in ( ρ h ), and by 20% due to a 39% decrease in ( a/d ) ratio. The proposed nonlinear finite element approach is efficient in determining the expected enhancement in shear capacity and ductility of SFRC corbels, and consequently in optimizing design parameters for such elements. Highlights: Validation / Parametric studies were performed on the experimentally tested SFRC corbels from the literature. Constitutive relations for fibrous concrete are included. The proposed numerical approach is a good tool for modelling SFRC corbels with constant or with variable depths.